2007
DOI: 10.4049/jimmunol.179.6.3995
|View full text |Cite
|
Sign up to set email alerts
|

Function and Regulation of SPLUNC1 Protein in Mycoplasma Infection and Allergic Inflammation

Abstract: Respiratory infections, including Mycoplasma pneumoniae (Mp), contribute to asthma pathobiology. To date, the mechanisms underlying the increased susceptibility of asthmatics to airway Mp infection remain unclear. Short palate, lung, and nasal epithelium clone 1 (SPLUNC1) protein is a recently described large airway epithelial cell-derived molecule that was predicted to exert host defense activities. However, SPLUNC1 function and regulation in an infectious or allergic milieu are still unknown. We determined h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
151
5
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(168 citation statements)
references
References 39 publications
10
151
5
2
Order By: Relevance
“…7B, C). Thus, our data show that IAV bound 178 predominantly to ciliated cells that were BPIFA1-negative, 2, 3 post infection but this is followed by a decrease over 2 -7 days 15,18,40 . Our results in 252 vivo extend these observations using IAV (Figs.…”
Section: Bpifa1 Expression After Iav Infection 42mentioning
confidence: 64%
See 1 more Smart Citation
“…7B, C). Thus, our data show that IAV bound 178 predominantly to ciliated cells that were BPIFA1-negative, 2, 3 post infection but this is followed by a decrease over 2 -7 days 15,18,40 . Our results in 252 vivo extend these observations using IAV (Figs.…”
Section: Bpifa1 Expression After Iav Infection 42mentioning
confidence: 64%
“…It has also been shown to have anti-10 bacterial roles. For example, Bpifa1 expression is induced after Mycoplasma 11 infection, enhancing IL-8 production and bacterial clearance 15 . BPIFA1 also has a 12 role in defense against Klebsiella pneumoniae 16 , possibly acting through modulation 13 of macrophage function 17 .…”
mentioning
confidence: 99%
“…However, this hypothesis is controversial, and some investigators have found that SPLUNC1 appears to have little antimicrobial activity against Escherichia coli, Listeria monocytogenes, or Pseudomonas aeruginosa (17), and does not appear to bind lipopolysaccharide (15). However, SPLUNC1 has recently been shown to inhibit Mycoplasma pneumoniae in airway cultures (28), and bind to lipopolysaccharide and disrupt Epstein-Barr virus proliferation (29). Although there is no current explanation for these discrepancies, we do not know whether SPLUNC1 is posttranslationally modified and/or how labile SPLUNC1 is once purified, and it is possible that the purification and storing of SPLUNC1 may alter its biological activity, leading to differing results.…”
Section: Resultsmentioning
confidence: 99%
“…Because SPLUNC1 is secreted by proximal airways, we propose that this regulation primarily occurs in the proximal airways, with little effect in the distal airways. However, if SPLUNC1 secretion is indeed up-regulated by inflammation (28), this secretion may serve to decrease ENaC activity and increase mucus clearance in the distal airways during these times. In conclusion, ENaC is a soluble regulator of ENaC that is expressed in multiple organs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation